INFLUENCE OF MODIFIED BIOFLAVONOIDS UPON EFFECTOR LYMPHOCYTES IN MURINE MODEL OF CONTACT SENSITIVITY - D. Z. Albegova; S. I. Pavlova; O. S. Laptev; V. V. Negrebetsky; A. A. Kyagova; L. A. Kozyr; J. K. Albegova; I. G. Kozlov (Медицинская иммунология, 2015)
Contact sensitivity reaction (CSR) to 2,4-dinitrofluorobenzene (DNFB) in mice is a model of in vivo immune response, being an experimental analogue to contact dermatitis in humans. CSR sensitization phase begins after primary contact with antigen, lasting for 10-15 days in humans, and 5-7 days, in mice. Repeated skin exposure to the sensitizing substance leads to its recognition and triggering immune inflammatory mechanisms involving DNFB-specific effector T lymphocytes. The CSR reaches its maximum 18-48 hours after re-exposure to a hapten. There is only scarce information in the literature about effects of flavonoids on CSR, including both stimulatory and inhibitory effects. Flavonoids possessed, predominantly, suppressive effects against the CSR development. In our laboratory, a model of contact sensitivity was reproduced in CBA mice by means of cutaneous sensitization by 2,4-dinitrofluorobenzene. The aim of the study was to identify the mechanisms of immunomodulatory action of quercetin dihydrate and modified bioflavonoids, using the method of adoptive transfer contact sensitivity by splenocytes and T-lymphocytes. As shown in our studies, a 30-min pre-treatment of splenocytes and T-lymphocytes from sensitized mice with modified bioflavonoids before the cell transfer caused complete prevention of contact sensitivity reaction in syngeneic recipient mice. Meanwhile, this effect was not associated with cell death induction due to apoptosis or cytotoxicity. Quercetin dihydrate caused only partially suppression the activity of adaptively formed T-lymphocytes, the contact sensitivity effectors. It was shown that the modified bioflavonoid more stronger suppress adoptive transfer of contact sensitivity in comparison with quercetin dehydrate, without inducing apoptosis of effector cells. Thus, the modified bioflavonoid is a promising compound for further studies in a model of contact sensitivity, due to its higher ability to suppress transfer of CSR with T-lymphocytes, as compared to quercetin dihydrate.